Regional Arthroscopy - Bagaria, Vaibhav (IntechOpen, 2013)
Arthroscopy has now become the most commonly performed musculoskeletal procedure. Arthroscopy has had several beneficial effects especially in terms of reduction of morbidity and reducing and in many cases eliminating the need for hospitalization. It all began with the knee surgeries and even today the most common arthroscopic procedures are performed in knee and yet arthroscopic surgeries performed for other regions right from temperomandibular joint down to the subtalar joint have replicated the success shown in knee surgeries. They are gradually becoming popular and this book intends to describe the tips and tricks employed by the experts in their respective field for benefit of the residents and fellows. This book has brought the experts in the field of the arthroscopy who have written the chapters concerning various regions viz Temporomandibular joint, Shoulder, Wrist, Lumbar Spine, Knee, Ankle, and the Subtalar Joint. The focus has been on delivering key surgical points that will help ensure that learning is seamless.